Pengaruh Pemberian Pupuk Anorganik dan Pupuk Organik Cair Terhadap Pertumbuhan Dan Hasil Tanaman Tomat (Lycopersicum esculentum Mill) - Vega Dorthea Rumbarak; Bagyono Bagyono; Margo Yuwono; Florentina H. Listyorini (Agrotek, 2017)
The study was aimed to identify the effect of anorganic and liquid organic fertilizer addition to the growth and yield of tomato. Potted research was conducted in split plot design which is based in completely randomized designed. There were 2 treatment factors being used, namely anorganic fertilizer as the main plot while the sub plot was organic fertilizer. The results revealed that the organich fertilizer only significantly affected plant’s fruit weight and average fruit weight. Bioleaf was found to be the best liquid organic fertilizer.